Intrahalocline eddies in the Amundsen Basin observed in the distributed network from the MOSAiC expedition - Alejandra Quintanilla-Zurita; Benjamin Rabe; Claudia Wekerle; Torsten Kanzow; Ivan Kuznetsov; Sinhue Torres-Valdes; Enric Pallàs-Sanz; Ying-Chih Fang (Ocean Science, 2026)
Hydrographic and velocity observations from the Multidisciplinary Drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition (2019–2020) reveal the presence of nine intrahalocline eddies (IHEs) in the Amundsen Basin during the winter drift of the Distributed Network (DN). Despite their relevance for Arctic stratification and mixing, IHEs in the Amundsen Basin remain poorly documented. Our study addresses this gap by providing the first detailed characterisation based on coordinated in situ hydrographic and velocity observations during wintertime. Eddies were identified as isopycnal displacements in Ice-Tethered Profiler (ITP) data. Additionally, by assessing rotational velocity signatures from Acoustic Doppler Current Profiler (ADCP) measurements, we applied a centre-detection method based on maximum swirl velocity (MSV). Nine anticyclonic eddies were observed, with radii ranging from 3.7 to 8.4 km and vertical extents between 23 and 80 m. Most eddies exhibited solid-body rotation in their cores, with maximum azimuthal velocities of up to 0.28 m s−1 and localised shallowing of the mixed layer by over 10 m. Water mass analysis showed that the eddy cores contained Eurasian halocline waters with consistent anomalies in temperature, salinity, and density relative to surrounding profiles, allowing us to infer pre-existing stratification conditions and offering clues to their origin. The observed eddy scales lie close to or slightly below the first baroclinic Rossby deformation radius of approximately 6.9 km, placing them in the (sub)mesoscale dynamical regime and suggesting a transitional balance where both geostrophic and cyclogeostrophic effects may be relevant. The MSV method yields systematically larger eddy radius estimates up to 25 % greater than traditional detection techniques that rely on velocity profiles or isopycnal displacements alone. This correction to the radius is essential, as it provides a more realistic measure of eddy size and dynamics under ice-covered conditions and could improve comparability across under-ice eddy studies. Although specific generation mechanisms remain uncertain, thermohaline signatures suggest that shallow local convection and baroclinic instability play a role in their formation. Our results provide new insights into the dynamics of under-ice eddies and their potential impact on Arctic oceanography and climate processes, addressing essential gaps in understanding polar mesoscale dynamics.

SalaciaML-2-Arctic — a deep learning quality control algorithm for Arctic Ocean temperature and salinity data - Sebastian Mieruch; Gastón Kreps; Mohamed Chouai; Felix Reimers; Myriel Vredenborg; Benjamin Rabe; Sandra Tippenhauer; Axel Behrendt (Frontiers in Marine Science, 2025)
We have extended a classical quality control (QC) algorithm by integrating a deep learning neural network, resulting in SalaciaML-2-Arctic , a tool for automated QC of Arctic Ocean temperature and salinity profile data. The neural network component was trained on the Unified Database for Arctic and Subarctic Hydrography (UDASH), which has been quality-controlled and labeled by expert oceanographers. SalaciaML-2-Arctic successfully reproduces human expertise by correcting misclassifications made by the classical algorithm, reducing False Negatives (samples incorrectly classified as “bad”) by 96% for temperature and 99% for salinity. When used in combination with a visual post-QC by human experts, it achieves a workload reduction of approximately 60% for temperature and 85% for salinity. All code and data required to reproduce the analysis or apply the method to other datasets are openly available via PANGAEA and GitHub. Moreover, SalaciaML-2-Arctic is accessible as a browser-based application at https://mvre.autoqc.cloud.awi.de , enabling its use without software installation or programming knowledge.

Broadening the horizon in land use change modelling: Normative scenarios for nature positive futures in Switzerland - Benjamin Black; Antoine Adde; Daniel Farinotti; Antoine Guisan; Nathan Külling; Manuel Kurmann; Caroline Martin; Paula Mayer; Sven-Erik Rabe; Jan Streit; Harry Zekollari; Adrienne Grêt-Regamey (Regional Environmental Change, 2024)
Within scenario-based research of social-ecological systems, there has been a growing recognition of the importance of normative scenarios that define positive outcomes for both nature and society. While several frameworks exist to guide the co-creation of normative scenario narratives, examples of operationalizing these narratives in quantitative simulation modelling are still limited. To address this gap, this paper presents an example of how aspects of normative scenarios can be realized within a spatial model of land use and land cover change. This is achieved through a combination of data-driven approaches to encapsulate scenario-specific differences in local and global scale phenomena, as well as iterative expert elicitation to quantify descriptive trends from narratives. This approach is demonstrated with a case study simulating five scenarios of landscape change (three normative and two exploratory) in Switzerland between 2020 and 2060. The resulting maps of future land use and land cover exhibited distinct variations between the scenarios, notably with regard to the prevalence of areas of heterogeneous semi-natural land, such as alpine pastures and grassland, often considered culturally emblematic of Switzerland. While the simulation results were generally consistent with the outcomes expressed in the scenario narratives, following a process of expert feedback, we reflect that there are clear challenges in leveraging such results to elicit further discussions as to the desirability and plausibility of future scenarios. Specifically, the need to summarize spatial simulations in a manner that is easily interpretable and encourages consideration of the broader patterns of change rather than focusing on fine-scale details.

Dynamical reconstruction of the upper-ocean state in the central Arctic during the winter period of the MOSAiC expedition - Ivan Kuznetsov; Benjamin Rabe; Alexey Androsov; Ying-Chih Fang; Mario Hoppmann; Alejandra Quintanilla-Zurita; Sven Harig; Sandra Tippenhauer; Kirstin Schulz; Volker Mohrholz; Ilker Fer; Vera Fofonova; et al. (Ocean Science, 2024)
This paper presents a methodological tool for dynamic reconstruction of the state of the ocean, based, as an example, on observations from the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) experiment. The data used in this study were collected in the Amundsen Basin between October 2019 and January 2020. Analysing observational data to assess tracer field and upper-ocean dynamics is highly challenging when measurement platforms drift with the ice pack due to continuous drift speed and direction changes. We have equipped the new version of the coastal branch of the global Finite-volumE sea ice–Ocean Model (FESOM-C) with a nudging method. Model nudging was carried out assuming a quasi-steady state. Overall, the model can reproduce the lateral and vertical structure of the temperature, salinity, and density fields, which allows for projecting dynamically consistent features of these fields onto a regular grid. We identify two separate depth ranges of enhanced eddy kinetic energy located around two maxima in buoyancy frequency: the depth of the upper halocline and the depth of the warm (modified) Atlantic Water. Simulations reveal a notable decrease in surface layer salinity and density in the Amundsen Basin towards the north but no significant gradient from east to west. However, we find a mixed-layer deepening from east to west, with a 0.084 m km−1 gradient at 0.6 m km−1 standard deviation, compared to a weak deepening from south to north. The model resolves several stationary eddies in the warm Atlantic Water and provides insights into the associated dynamics. The model output can be used to further analyse the thermohaline structure and related dynamics associated with mesoscale and submesoscale processes in the central Arctic, such as estimates of heat fluxes or mass transport. The developed nudging method can be utilized to incorporate observational data from a diverse set of instruments and for further analysis of data from the MOSAiC expedition.

Introduction to the Special Issue on the New Arctic Ocean - Thomas Weingartner; Carin Ashjian; Lawson Brigham; Thomas Haine; Liza Mack; Don Perovich; Benjamin Rabe (Oceanography, 2022)
One hundred and thirty years ago, Fridtjof Nansen, the Norwegian polar explorer and scientist, set off on a bold three-year journey to investigate the unknown Arctic Ocean. The expedition relied on a critical technological development: a small, strong, and maneuverable vessel, powered by sail and an engine, with an endurance of five years for twelve men. His intellectual curiosity and careful observations led to an early glimpse of the Arctic Ocean’s circulation and its unique ecosystem. Some of Nansen’s findings on sea ice and the penetration of Atlantic Water into the Arctic Ocean established a benchmark against which we have measured profound changes over the past few decades. In contrast, little was known about the Arctic Ocean’s ecosystem processes prior to the onset of anthropogenic climate change. Nansen’s successes, which paved the way for subsequent research, were gained in part from Indigenous Greenlanders who taught him how to survive in this harsh environment.

Freshwater in the Arctic Ocean 2010–2019 - Amy Solomon; Céline Heuzé; Benjamin Rabe; Sheldon Bacon; Laurent Bertino; Patrick Heimbach; Jun Inoue; Doroteaciro Iovino; Ruth Mottram; Xiangdong Zhang; Yevgeny Aksenov; Ronan McAdam; et al. (Ocean Science, 2021)
The Arctic climate system is rapidly transitioning into a new regime with a reduction in the extent of sea ice, enhanced mixing in the ocean and atmosphere, and thus enhanced coupling within the ocean–ice–atmosphere system; these physical changes are leading to ecosystem changes in the Arctic Ocean. In this review paper, we assess one of the critically important aspects of this new regime, the variability of Arctic freshwater, which plays a fundamental role in the Arctic climate system by impacting ocean stratification and sea ice formation or melt. Liquid and solid freshwater exports also affect the global climate system, notably by impacting the global ocean overturning circulation. We assess how freshwater budgets have changed relative to the 2000–2010 period. We include discussions of processes such as poleward atmospheric moisture transport, runoff from the Greenland Ice Sheet and Arctic glaciers, the role of snow on sea ice, and vertical redistribution. Notably, sea ice cover has become more seasonal and more mobile; the mass loss of the Greenland Ice Sheet increased in the 2010s (particularly in the western, northern, and southern regions) and imported warm, salty Atlantic waters have shoaled. During 2000–2010, the Arctic Oscillation and moisture transport into the Arctic are in-phase and have a positive trend. This cyclonic atmospheric circulation pattern forces reduced freshwater content on the Atlantic–Eurasian side of the Arctic Ocean and freshwater gains in the Beaufort Gyre. We show that the trend in Arctic freshwater content in the 2010s has stabilized relative to the 2000s, potentially due to an increased compensation between a freshening of the Beaufort Gyre and a reduction in freshwater in the rest of the Arctic Ocean. However, large inter-model spread across the ocean reanalyses and uncertainty in the observations used in this study prevent a definitive conclusion about the degree of this compensation.

A Framework for the Development, Design and Implementation of a Sustained Arctic Ocean Observing System - Craig M. Lee; Sandy Starkweather; Hajo Eicken; Mary-Louise Timmermans; Jeremy Wilkinson; Stein Sandven; Dmitry Dukhovskoy; Sebastian Gerland; Jacqueline Grebmeier; Janet M. Intrieri; Sung-Ho Kang; Molly McCammon; et al. (Frontiers in Marine Science, 2019)

Evolving the Physical Global Ocean Observing System for Research and Application Services Through International Coordination - Bernadette M. Sloyan; John Wilkin; Katherine Louise Hill; Maria Paz Chidichimo; Meghan F. Cronin; Johnny A. Johannessen; Johannes Karstensen; Marjolaine Krug; Tong Lee; Eitarou Oka; Matthew D. Palmer; Benjamin Rabe; et al. (Frontiers in Marine Science, 2019)

Decorrelation scales for Arctic Ocean hydrography – Part I: Amerasian Basin - Hiroshi Sumata; Frank Kauker; Michael Karcher; Benjamin Rabe; Mary-Louise Timmermans; Axel Behrendt; Rüdiger Gerdes; Ursula Schauer; Koji Shimada; Kyoung-Ho Cho; Takashi Kikuchi (Ocean Science, 2018)
Any use of observational data for data assimilation requires adequate information of their representativeness in space and time. This is particularly important for sparse, non-synoptic data, which comprise the bulk of oceanic in situ observations in the Arctic. To quantify spatial and temporal scales of temperature and salinity variations, we estimate the autocorrelation function and associated decorrelation scales for the Amerasian Basin of the Arctic Ocean. For this purpose, we compile historical measurements from 1980 to 2015. Assuming spatial and temporal homogeneity of the decorrelation scale in the basin interior (abyssal plain area), we calculate autocorrelations as a function of spatial distance and temporal lag. The examination of the functional form of autocorrelation in each depth range reveals that the autocorrelation is well described by a Gaussian function in space and time. We derive decorrelation scales of 150–200 km in space and 100–300 days in time. These scales are directly applicable to quantify the representation error, which is essential for use of ocean in situ measurements in data assimilation. We also describe how the estimated autocorrelation function and decorrelation scale should be applied for cost function calculation in a data assimilation system.

Aerosol emissions of a ship diesel engine operated with diesel fuel or heavy fuel oil - Thorsten Streibel; Jürgen Schnelle-Kreis; Hendryk Czech; Horst Harndorf; Gert Jakobi; Jorma Jokiniemi; Erwin Karg; Jutta Lintelmann; Georg Matuschek; Bernhard Michalke; Laarnie Müller; Jürgen Orasche; et al. (Environmental Science and Pollution Research, 2017)